2-Aroylquinoline-5, 8-diones as potent anticancer agents displaying tubulin and heat shock protein 90 (HSP90) inhibition. Issue 2 (17th November 2015) - Nepali, Kunal; Kumar, Sunil; Huang, Hsiang-Ling; Kuo, Fei-Chiao; Lee, Cheng-Hsin; Kuo, Ching-Chuan; Yeh, Teng-Kuang; Li, Yu-Hsuan; Chang, Jang-Yang; Liou, Jing-Ping; Lee, Hsueh-Yun
Abstract : This study reports the synthesis of a series of 2-aroylquinoline-5, 8-diones (11–23 ) on the basis of scaffold hopping. Abstract : This study reports the synthesis of a series of 2-aroylquinoline-5, 8-diones (11–23 ) on the basis of scaffold hopping. The presence of a methoxy group at C6 assists the highly regioselective incorporation with various amines, and simplifies the structural identification process. Among the synthetic compounds, 6-dimethylamino-2-(3, 4, 5-trimethoxybenzoyl)-quinoline-5, 8-dione (12 ) and 7-pyrrolidin-1-yl-2-(3, 4, 5-trimethoxybenzoyl)-quinoline-5, 8-dione (23 ) exhibit remarkable anti-proliferative activity against the cancer cell lines tested with mean IC50 values of 0.14 and 0.27 μM, respectively. Compound23 showed moderate inhibitory activity against tubulin polymerization with an IC50 value of 5.9 μM. In a western blot analysis, 23 caused induction of HSP70 and degradation of Akt, revealing that it possesses HSP90 inhibitory activity.